2015
DOI: 10.1177/0954411915595433
|View full text |Cite
|
Sign up to set email alerts
|

The increase in cobalt release in metal-on-polyethylene hip bearings in tests with third body abrasives

Abstract: Hypersensitivity reactions in patients receiving metal-on-metal hip replacements have been attributed to corrosion products as observed by elevated cobalt and chromium ions in the blood. Although the majority of cases are reported in metal-on-metal, incidences of these reactions have been reported in the metal-on-polyethylene patient population. To date, no in vitro study has considered cobalt release for this bearing combination. This study considered four 28 mm and seven 52 mm diameter metal-on-polyethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A clinical study showed that patients with a dual‐taper MoP hip system had much higher Co level in serum than patients with nonmodular stem MoP hip system (Gill, Webb, Sloan, & Beaver, ), suggesting that fretting corrosion was an important releasing source of Co ions. The effect of tribocorrosion in articulation on metal ions in serum of patients with MoP hip implants was not clear although a laboratory study demonstrated an increased Co release with third‐body abrasive at articulating surface in a MoP hip system (De Villiers, Traynor, Collins, & Shelton, ). In this study, we observed that those cases with minimal fretting corrosion but evident tribocorrosion showed relatively high Co and Cr ions in serum (Table , MoP5, and MoP10).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study showed that patients with a dual‐taper MoP hip system had much higher Co level in serum than patients with nonmodular stem MoP hip system (Gill, Webb, Sloan, & Beaver, ), suggesting that fretting corrosion was an important releasing source of Co ions. The effect of tribocorrosion in articulation on metal ions in serum of patients with MoP hip implants was not clear although a laboratory study demonstrated an increased Co release with third‐body abrasive at articulating surface in a MoP hip system (De Villiers, Traynor, Collins, & Shelton, ). In this study, we observed that those cases with minimal fretting corrosion but evident tribocorrosion showed relatively high Co and Cr ions in serum (Table , MoP5, and MoP10).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Although the majority of cases of hypersensitivity reactions attributed to corrosion products and elevation of cobalt and chromium ions in the blood were reported in metal-onmetal (MOM) implants, [15][16][17] these reactions have been also reported in the metal-on-polyethylene patients. 18 Although Bijukumar et al 19 showed that the metal wear rate of MOM articulation is approximately 20 times lower than that of MOP articulation, the polyethylene particle wear is reduced in the recently introduced highly cross-linked polyethylene. 20 Scully and Teeny 21 reported pseudo-tumor formation in a case of MOP total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“… Number of studies using either a particle method or scratching the implant surfaces directly and the bearing material combinations used in these, where multiple materials have been investigated, both material combinations have been included, materials characterised as ‘other’ include bearing materials such as PEEK and oxidised zirconium. [ 15 , 23 , 28 , 29 , [31] , [32] , [33] , 42 , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ...…”
Section: Methods For Simulation Of Third Body Wearmentioning
confidence: 99%
“…6 The number of studies using bone, PMMA and metal particles in third body wear simulation; other includes particles such as bone void fillers and hydroxyapatite. [ 15 , 23 , 28 , 29 , 33 , 39 , 42 , 45 , 52 , 54 , 55 , 59 , 61 , 62 , [70] , [71] , [72] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [83] , [84] , [85] , 87 , 89 , 90 , 92 , 93 ]. …”
Section: Methods For Simulation Of Third Body Wearmentioning
confidence: 99%